Profile of the critical thinking skills of blind students in solving geometry problems based on academic ability - Adhetia Martyanti; Suhartini (STKIP PGRI Banjarmasin, 2019)
This study aims to describe the critical thinking skills of blind students in solving geometry problems in terms of the level of academic ability. This research is qualitative research with a descriptive approach. The research subjects consisted of three blind students in class VIII MTsLB Yaketunis, Yogyakarta. Data was collected through tests of critical thinking skills and interviews. Triangulation is carried out as an effort to guarantee the validity of the data. Furthermore, the results of the study indicate that there are differences in the profile of the critical thinking abilities of blind students in solving geometry problems in terms of the level of academic ability. Blind students with high and moderate academic abilities show 3 and 1 of 5 indicators of critical thinking abilities, respectively. Whereas for blind students with low academic ability, indicators of critical thinking skills have not yet emerged. The results of this study are expected to be a consideration for teachers in designing learning geometry that can facilitate the development of students' critical thinking skills of the blind